2020
DOI: 10.3390/nu12071983
|View full text |Cite
|
Sign up to set email alerts
|

A Revolutionizing Approach to Autism Spectrum Disorder Using the Microbiome

Abstract: The study of human microbiota and health has emerged as one of the ubiquitous research pursuits in recent decades which certainly warrants the attention of both researchers and clinicians. Many health conditions have been linked to the gut microbiota which is the largest reservoir of microbes in the human body. Autism spectrum disorder (ASD) is one of the neurodevelopmental disorders which has been extensively explored in relation to gut microbiome. The utilization of microbial knowledge promises a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 179 publications
1
29
0
1
Order By: Relevance
“…The gut microbiome consists of a mixture of microbes that can be beneficial (i.e., commensal bacteria), and a relatively small portion of them may pose as a disease risk to us ( Thursby and Juge, 2017 ; Bresalier and Chapkin, 2020 ). Apart from infections, any changes in the equilibrium in the microbial population in the gut have shown to cause or associate with the development of diseases like inflammatory bowel diseases, neuropsychiatric-related diseases, or even cancer ( Lee et al, 2019 ; Johnson et al, 2020 ; Ternes et al, 2020 ; Lee and Chang, 2021 ). As much as gut microbiome composition is affected by diet, recent data have also pointed out that microbes in the gut have functional importance in nutrients and also drug metabolisms ( Hooper et al, 2002 ; Ash, 2019 ; Maini Rekdal et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiome consists of a mixture of microbes that can be beneficial (i.e., commensal bacteria), and a relatively small portion of them may pose as a disease risk to us ( Thursby and Juge, 2017 ; Bresalier and Chapkin, 2020 ). Apart from infections, any changes in the equilibrium in the microbial population in the gut have shown to cause or associate with the development of diseases like inflammatory bowel diseases, neuropsychiatric-related diseases, or even cancer ( Lee et al, 2019 ; Johnson et al, 2020 ; Ternes et al, 2020 ; Lee and Chang, 2021 ). As much as gut microbiome composition is affected by diet, recent data have also pointed out that microbes in the gut have functional importance in nutrients and also drug metabolisms ( Hooper et al, 2002 ; Ash, 2019 ; Maini Rekdal et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…when the Greek physician Hippocrates said, “death is in the bowels” and also “poor digestion is the origin of all evil” ( Iebba et al, 2016 ). Over the years, researchers have discovered that there are strong correlations between the gut microbiome and important systems in the human body, such as the brain in the nervous system and the immune system that protects the body against deadly infections and cancer ( Schwabe and Jobin, 2013 ; Gonzalez-Perez and Lamousé-Smith, 2017 ; Yang and Jobin, 2017 ; Chew et al, 2020 ; Johnson et al, 2020 ; Lee et al, 2021 ). Existing evidence has demonstrated that gut dysbiosis can contribute to the etiology of numerous human diseases, including diabetes, atherosclerosis, inflammatory bowel disease, atopic dermatitis, autism, or even the development of cancer ( Adlerberth et al, 2007 ; Michail et al, 2012 ; Morgan et al, 2012 ; Mulle et al, 2013 ; Vinje et al, 2014 ; Zackular et al, 2014 ; Song et al, 2016 ; Gózd-Barszczewska et al, 2017 ; Jie et al, 2017 ; Ni et al, 2017 ; Lee et al, 2020a , b ; Selvaraj et al, 2020 ; Wang et al, 2021 ).…”
Section: Importance Of Gut Microbiome In Diseasesmentioning
confidence: 99%
“…The most striking part was the presence of co-morbid disorders among these patients, particularly anxiety and depression. There is still an apparent lack of explanations as to how microbes in the gut communicate with neurons in the brain that drives behavioral or emotional changes, but more clues are emphasizing the importance of the gut–brain axis (Foster and Neufeld, 2013 ; Kennedy et al, 2014 ; Lee et al, 2018 , 2019 ; Quigley, 2018 ; Johnson et al, 2020 ). Coretti et al observed a substantial increase of Bacteroidetes and Proteobacteria , with a decrease of Actinobacteria in young children (aged 2–4 years of age) with autism spectrum disorder (ASD).…”
Section: How Does the Microbiome Reflect One's State Of Health?mentioning
confidence: 99%
“…This conceptualization has paved the way for scientists to explore and link various health conditions to the MGBA in an attempt to explain the possible etiopathologies involved in their occurrence. The number of studies involving some of the common disorders in the gastrointestinal, psychiatric, cardiometabolic and neurological domains, as well as cancers, in relation to the MGBA has been exponentially growing over recent decades and steadily moving towards a promising therapeutic direction in the context of human health [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The first colonization of microbes in humans is thought to occur during birth although there are studies suggesting that this could occur as early as in utero via placental colonization [9][10][11][12]. Various factors influence the composition of microbiota in an individual which can be classified into extrinsic and intrinsic factors [2,6]. The influence of these factors largely manifests as the result of a dynamic and complex interplay between the environment and the human microbiome in a way yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%